2023
DOI: 10.3390/lubricants11110459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Contamination, Iron Particles, and Energy Input on the NVH Behavior of Wet Clutches

Johannes Wirkner,
Mirjam Baese,
Astrid Lebel
et al.

Abstract: The driving comfort and safety of the automotive powertrain are significantly related to the performance, lifetime, and functionality of the lubricant. The presented study focuses on investigating the performance loss of the lubricant due to water contamination resulting from environmental influences and iron particles originating from the wear of different machine elements. The main purpose is to determine critical factors that contribute to the degradation of the lubricant, and increase the tendency to NVH b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Second, in terms of lubricant quality, Li et al [15] investigated the mechanism of the effect of lubricant on the friction characteristics of wet clutches and found that the lubricant mainly affected the friction coefficient through the formation of calcium carbonate on the friction surface. In addition, Wirkner et al [16] and Fatima et al [17] studied the influence of water content and iron filing content in the lubricant on the friction coefficient of wet clutches. Farfán-Cabrera et al [18] also investigated the influence of bio-lubricants on the friction coefficient of wet clutches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in terms of lubricant quality, Li et al [15] investigated the mechanism of the effect of lubricant on the friction characteristics of wet clutches and found that the lubricant mainly affected the friction coefficient through the formation of calcium carbonate on the friction surface. In addition, Wirkner et al [16] and Fatima et al [17] studied the influence of water content and iron filing content in the lubricant on the friction coefficient of wet clutches. Farfán-Cabrera et al [18] also investigated the influence of bio-lubricants on the friction coefficient of wet clutches.…”
Section: Introductionmentioning
confidence: 99%
“…friction surface. In addition, Wirkner et al [16] and Fatima et al [17] studied of water content and iron filing content in the lubricant on the friction coe clutches. Farfán-Cabrera et al [18] also investigated the influence of bio-lub friction coefficient of wet clutches.…”
Section: Introductionmentioning
confidence: 99%